Isolated in the caribbean :using genetic and ecotoxicological data to assess inshore habits of bottlenose dolphins in Bocas del Toro, Panama (2018)
The International Union for Conservation of Nature ? IUCN global conservation status for the bottlenose dolphins (Tursiops truncatus) is currently ?least concern?. However, in the Caribbean, small localized ?inshore form? populations of bottlenose dolphins may be in higher risk of extinction due to the combination of the relatively high population isolation, site fidelity, and strong anthropogenic pressures. Particularly, the population of dolphins in the Bocas del Toro Archipelago (Panama) shows high site fidelity, and it is characterized by high levels of dolphin-watching tourism activities happening in the area. Assessing inshore habits using both genetic and ecotoxicological data would provide needed information to change national conservation status and guarantee their conservation in the long-term. Following this, this Ph.D. thesis was developed with following aims 1) to establish population genetic structure and genetic diversity estimates of the bottlenose dolphins in Bocas del Toro in relation to the Caribbean; 2) to assess coastal habits of these dolphins using two ecological markers (stable isotopes and mercury concentrations); 3) to identify risk level for these dolphins to mercury exposition; 4) to discuss the relevance of using both genetic and ecotoxicological tools to delimit the bottlenose dolphin ecotypes; and 5) to compile and present all these scientific evidence to Panamanian government in order they implement an adequate management plan to protect this bottlenose dolphin population. Information presented in this work provides needed data to priories their national conservation, since isolation makes these animals vulnerable to several human activities, including exposition to mercury and not-regulated tour-boat traffic. It is recommended to the government of Panama that reevaluate the national conservation status of this bottlenose dolphin population, as preventive measure while a management plan is implemented in the Archipelago